TOWARDS GREEN SMART CITY THROUGH PROVIDING OPEN SPACE FOR CITIES IN INDONESIA: SYSTEMATIC AND BIBLIOMETRIC LITERATURE REVIEW - Rilansari, Valendya; Rahmah, Chania; Diyaulhaq, Wiedad (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Institut Teknologi Sumatera, Lampung Selatan, Lampung, Indonesia, 2024)
Smart cities become benchmarks in development cities around the world since the 1990s. In the urban planning context, there are concerns regarding the application of the smart city concept which is considered to only prioritize the progress of cities by technology however no notice to the ecological side of the city. This research discusses the development and arrangement of cities through planning that ensures ecosystem balance, one of which is through open space, which in this case is widely discussed that is green open space. The usual problem that occurs during the development of green open space is not enough land area for available allocation causing an imbalance ecosystem as well as against the sustainability concept. This research method studies literature systematic and bibliometric using Microsoft Excel and VOSviewer from discussion theory and policy about green open space that has been planned in various countries for can applied to cities in Indonesia. The analysis explains the discussion regarding green open space in connection to moving towards a green smart application to cities in Indonesia. Eventually, the findings from this research are discussed related to implementation in the cities in Indonesia which are divided into five aspects, namely political land development, community perception, infrastructure, landscape design, and socio-economic psychology. The final recommendation is that this aspect can be studied further to be applied to cities in Indonesia to realize city smart green future.